On rate of convergence of Fourier series of a function of WienerÂ´s class - Siddiqi, R. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The main object of this paper is to obtain the rate of convergence of Fourier series of a function of Wiener's class. From our theorem we can deduce a generalized version of a theorem of Wiener.